Low and moderate doses of ionizing radiation up to 2 Gy modulate transmigration and chemotaxis of activated macrophages, provoke an anti‐inflammatory cytokine milieu, but do not impact upon viability and phagocytic function. (January 2015) - Wunderlich, R.; Ernst, A.; Rödel, F.; Fietkau, R.; Ott, O.; Lauber, K.; Frey, B.; Gaipl, U. S.
Summary Benign painful and inflammatory diseases have been treated for decades with low/moderate doses of ionizing radiation (LD‐X‐irradiation). Tissue macrophages regulate initiation and resolution of inflammation by the secretion of cytokines and by acting as professional phagocytes. Having these pivotal functions, we were interested in how activated macrophages are modulated by LD‐X‐irradiation, also with regard to radiation protection issues and carcinogenesis. We set up an ex‐vivo model in which lipopolysaccharide pre‐activated peritoneal macrophages (pMΦ) of radiosensitive BALB/c mice, mimicking activated macrophages under inflammatory conditions, were exposed to X‐irradiation from 0·01 Gy up to 2 Gy. Afterwards, the viability of the pMΦ, their transmigration and chemotaxis, the phagocytic behaviour, the secretion of inflammatory cytokines and underlying signalling pathways were determined. Exposure of pMΦ up to a single dose of 2 Gy did not influence their viability and phagocytic function, an important fact regarding radiation protection. However, significantly reduced migration, but increased chemotaxis of pMΦ after exposure to 0·1 or 0·5 Gy, was detected. Both might relate to the resolution of inflammation. Cytokine analyses revealed that, in particular, the moderate dose of 0·5 Gy applied in low‐dose radiotherapy for inflammatory diseases results in an anti‐inflammatory cytokine microenvironment of pMΦ, as the secretion of the proinflammatory cytokine interleukin (IL)‐1β was reduced and that of the anti‐inflammatory cytokine transforming growth factor (TGF)‐β increased. Further, the reduced secretion of IL‐1β correlated with reduced nuclear translocation of nuclear factor (NF)‐κB p65, starting at exposure of pMΦ to 0·5 Gy of X‐irradiation. We conclude that inflammation is modulated by LD‐X‐irradiation via changing the inflammatory phenotype of macrophages.